2008
DOI: 10.1093/qjmed/hcn089
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between statins and clopidogrel: is there anything clinically relevant?

Abstract: Since their introduction several years ago, the 3-hydroxy-3-methylglutaryl coenzyme A (HMGCoA) reductase inhibitors-the statins-have been widely used for hyperlipidemia and for the primary/secondary prevention of cardiovascular diseases. They have been shown to be safe as well as efficacious in a number of different clinical trials; however, studies have suggested that they can interact with other co-administered therapies. More recently, the thienopyridines have been successfully integrated with the conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Simvastatin is a well tolerated drug, but its concentration-dependent muscle toxicity is a potentially serious adverse effect that has to be taken into consideration (Armitage 2007). The effect of simvastatin on the activation of clopidogrel has been studied widely due to concerns about the possibly reduced antiplatelet activity of clopidogrel in statin users (Vinholt et al, 2005;Bhindi et al, 2008;Siepmann et al, 2014). However, to our knowledge, the effect of clopidogrel on the pharmacokinetics of simvastatin has not been characterized previously.…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin is a well tolerated drug, but its concentration-dependent muscle toxicity is a potentially serious adverse effect that has to be taken into consideration (Armitage 2007). The effect of simvastatin on the activation of clopidogrel has been studied widely due to concerns about the possibly reduced antiplatelet activity of clopidogrel in statin users (Vinholt et al, 2005;Bhindi et al, 2008;Siepmann et al, 2014). However, to our knowledge, the effect of clopidogrel on the pharmacokinetics of simvastatin has not been characterized previously.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been suggested that this interaction is more likely with lipophilic statins, which share the same CYP450 metabolizing isoenzyme (Table 1 [66][67][68][69][70][71][72] ). However, discordance between ex vivo data, which points in favour of an interaction, and the majority of clinical studies, which failed to detect a clinically relevant effect, has to be acknowledged [72] . Lau et al [73] reiterated the contribution of CYP3A4 activity to the phenomenon of clopidogrel resistance.…”
Section: Clopidogrel Resistancementioning
confidence: 99%
“…There is some evidence to support a possible pharmacokinetic interaction between statins and clopidogrel. However, real-life interactions including hard end point studies seem to lack an association between the two drugs [57] . The United States FDA, on November 17, 2009, updated the public and health care professions about new safety information concerning a drug interaction between omeprazole and clopidogrel.…”
Section: Lin Sl Et Al Interaction Between Clopidogrel and Ppismentioning
confidence: 99%